PENGARUH PEMBERDAYAAN DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN BAGIAN PEMASARAN (PT MAYORA KOTA BENGKULU) - Galuh Dea Gayatri; Onsardi Onsardi (UM. Bengkulu, 2020)
The title of this research is the influence of empowerment and self efficacy to semployee performance at Sales Division (PT Mayora Kota Bengkulu). This research is based on important of performace in an organization. Perfomance can be influenced by several factors. The suspected factors are empowerment and self efficacy. This research aims to analyze the influence of empowerment and self efficacy to performance. The object of this research salesman in Sales Division at PT Mayora Kota Bengkulu with metode nonprobabilistic sampling method. The reason of choice this sample that the information needed can get by one group who have certainty information are sales employee. The method collected data by used questionnaire. Using multi linier regression data analysis technique, the result of this research can be concluded that empowerment and self efficacy have significant end positive influences to employee performance at sales division (PT Mayora Kota Bengkulu). Keywords : Empowerment, self efficacy and employee performance